2019
DOI: 10.1021/acs.jpca.9b05571
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Fukui Indices and Reactivity Descriptors Based on Sanderson’s Principle

Abstract: A previous study presented a very simple model mainly based on Sanderson’s principle for estimating important reactivity descriptors, such as the local hardness and the local electrophilicity. In another study, a new way of calculating the Fukui function was obtained that resulted in a new operative formula for the function. We also obtained the second-order partial derivative of the electron density with regard to the number of electrons. The current study analyzes the relationships between the two models and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…In a previous paper, we studied some possibilities for deriving a local electrophilicity and concluded that eq seems to be not only very simple, but at the same time a very reliable approach to this important property: where the term f k α (α = + , – or 0) corresponds to local Fukui functions, which are normally defined as: and (for neutral or radical attacks), where q k ( N 0 – 1), q k ( N 0 ), and q k ( N 0 + 1) are the electron populations associated with the k th atom (in the cation, neutral molecule, and anion, respectively). The electron populations should be calculated by using a particular population analysis (Hirshfeld’s analysis as an example).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper, we studied some possibilities for deriving a local electrophilicity and concluded that eq seems to be not only very simple, but at the same time a very reliable approach to this important property: where the term f k α (α = + , – or 0) corresponds to local Fukui functions, which are normally defined as: and (for neutral or radical attacks), where q k ( N 0 – 1), q k ( N 0 ), and q k ( N 0 + 1) are the electron populations associated with the k th atom (in the cation, neutral molecule, and anion, respectively). The electron populations should be calculated by using a particular population analysis (Hirshfeld’s analysis as an example).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper, 24 we studied some possibilities for deriving a local electrophilicity 25 and concluded that eq 20 seems to be not only very simple, but at the same time a very reliable approach to this important property:…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [32], a methodology was defined to obtain bond reactivity indices for the NBOs (fiNBO and fi+NBO indices in Equations () and ()) that is based on the regression that can be seen in Equations () and (), which provide reactivity indices for bond orbitals instead of the atoms in the molecule. Bond index is not a new concept as it was previously proposed by Bultinck et al [33].…”
Section: Description and Fundamentals Of The New Model Why Choose Nat...mentioning
confidence: 99%
“…The parabolic approximation [11] is usually expressed as: ΔEμΔN+12ηΔN2. But, in Reference [29], the author justifies the use of a cubic expansion of the shape: ΔEAμ·ΔNA+12ηAΔNA2+16·normalΩA·ΔNA3, in the local case (atoms in the molecule), where normalΩA=()3ΔEANA3ΔN=0. Moreover, the local chemical potentials of the atoms in equilibrium (and the corresponding ions) should satisfy (principle of electronegativity equalization): μA0=μB0==μk0=μ, μA+=μB+==μk+=μ+, μA=μB==μk=μ, where A , B ,… k refer to the atoms of the molecule, and μ , μ + , and μ − to the global electronic chemical potentials of the neutral molecule, cation and anion, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleophilic attack, f + (r) = q r (N+1)-q r (N) Electrophilic attack, f -(r) = q r (N) -q r (N-1) Radial attack, f o (r) = [q r (N+1)-q r (N-1)]/2 Dual descriptor, ∆f(r)= f + (r)-f -(r) where q r corresponds to atomic charge evaluated from mulliken charge, N corresponds to atomic charge, (N+1) corresponds to cationic state and (N-1) corresponds to anionic state [48][49][50]. Regions in chemical species with the highest values of the Fukui function (fj) demonstrate significant reactivity for comparable attacks, according to Parr and Yang et al [50].…”
Section: Fukui Functionmentioning
confidence: 99%